2015
DOI: 10.1080/15389588.2015.1067693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vehicle-Based Crash Severity Metrics

Abstract: The broad findings of this study suggest it is feasible to improve injury prediction if we consider adding restraint performance to classic measures, e.g. delta-v. Applications, such as advanced automatic crash notification, should consider the use of different metrics for belted versus unbelted occupants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Impact velocity was investigated as a plausible predictor as it is controllable and it has previously been reported that with a spring‐mounted simulated maxillary arch, increased impact speed led to an increase in the number of teeth broken during impact 18 . Various measures of velocity change during impact can allow estimation of, and have been invoked previously either directly or indirectly in, functionals for injury likelihood estimation in automotive crashworthiness testing 27 . The change in velocity of the impactor and the velocity of the dentition after impact can be interpreted as proxy measures for the change in momentum during impact, which is dictated by the stiffness of the dentition and the spring‐anvil system 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impact velocity was investigated as a plausible predictor as it is controllable and it has previously been reported that with a spring‐mounted simulated maxillary arch, increased impact speed led to an increase in the number of teeth broken during impact 18 . Various measures of velocity change during impact can allow estimation of, and have been invoked previously either directly or indirectly in, functionals for injury likelihood estimation in automotive crashworthiness testing 27 . The change in velocity of the impactor and the velocity of the dentition after impact can be interpreted as proxy measures for the change in momentum during impact, which is dictated by the stiffness of the dentition and the spring‐anvil system 18 .…”
Section: Discussionmentioning
confidence: 99%
“…18 Various measures of velocity change during impact can allow estimation of, and have been invoked previously either directly or indirectly in, functionals for injury likelihood estimation in automotive crashworthiness testing. 27 The change in velocity of the impactor and the velocity of the dentition after impact can be interpreted as proxy measures for the change in momentum during impact, which is dictated by the stiffness of the dentition and the spring-anvil system. 18 Traumatic loading to the periodontal support has been shown to decrease the stiffness of the TPBC system, 21 arguably altering the change in momentum.…”
Section: Discussionmentioning
confidence: 99%
“…The Vehicle Pulse Index (VPI) which measures the relative strength of the collision waveform to the occupant in the vehicle uses a single-degree-of-freedom mass spring model (Tsoi and Gabler, 2015). The model consists of mass M, which represents the occupant, spring k and slack s, which represent the constraint system.…”
Section: Collision Strengthmentioning
confidence: 99%
“…Injury intensity coefficients are adopted for the evaluation of the efficiency of the safety systems in the area of road constructions and vehicles, both passive and active. The coefficients may be based on the kinematics of the ATD phantom (anthropometric test device) [5] or of a vehicle [6]. Delta-v parameter which specifies the decrease of vehicle velocity as a result of an impact is the most frequently applied and the simplest in calculation coefficient based on the vehicle kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the ASI parameter has been proved in numerous publications the authors of which strive to prove the dependence between its value and the injuries suffered by accident victims [9][10][11] or try to propose models allowing for estimation of ASI value depending on factors such as the impact conditions or mechanical properties of the tested road infrastructure [12]. Equipping vehicles in an EDR system (Event Data Records) which records data such as vehicle motion, seat belt fastening, or operation of active safety systems in vehicles currently allows for the determination of correlations between injury intensity factors and real injuries suffered as a result of road collisions [6,13]. ASI is a good indicator in the scope of injuries suffered by passengers having their seat belts fastened and for the vehicles equipped with airbags.…”
Section: Introductionmentioning
confidence: 99%